“Help your son to improve his speech” (Journal of Parents and Teachers, 2013)
This article deals with the importance of the families in their children’s language development. Starting from the idea that each child follows a different developmental rhythm that should be respected, the author defends that it is essential the dialogue between family and child. She presents different pieces of advices about what and how to talk with the children. She also shows how to act in those cases where the child communicates incorrectly. She refers to frequent mistakes that families do and contributes with strategies that favor the language improvement.
Keywords: Language development; family; communication; strategy; didactic; education.